Five kingdoms a multimedia guide to the phyla of life on earth - Margulis, L. (Amsterdam : Expert Center for Taxonomic Identification, 1996)
This CD-ROM guide provides multimedia information covering all of the 92 phyla living today with examples from selected genera
System requirements: IBM compatible PC with 80486 processor, 8MB RAM, Windows 3.1 or Windows 95, VGA 16 bit colour monitor, quad-speed CD-ROM player, soundcard compatible with Windows
Keywords: Biology -- Classification; Phyla (Genus)